GRAPHITE PSEUDOMORPHS AFTER DIAMOND? A CARBON ISOTOPE AND SPECTROSCOPIC STUDY OF GRAPHITE CUBOIDS FROM THE MAKSYUTOV COMPLEX, SOUTH URAL MOUNTAINS, RUSSIA - Leech M.L.; Ernst W.G. (My University, 1998)
Unusual cuboid graphite aggregates (up to 13 mm edge length) from the eclogitic gneiss unit of the Maksyutov Complex deflect a foliation defined by groundmass graphite and phengite, and pressure shadows have developed around these blocky aggregates. Carbon isotope ratios, δ13C/12C, for the cuboid graphite range from about −24 to −42‰, demonstrating that these rocks have retained an original biogenic carbon signature. X-ray diffraction, laser Raman spectroscopy, infrared spectroscopy, and transmission electron microscopy indicate that graphite is well-crystallized with minor defects; no relict organic compounds were detected. Comparisons of these cuboid aggregates with thin sections and scanning electron microscope images of proven graphitized diamonds from the Beni Bousera peridotite massif show that Maksyutov graphite is similar. Laboratory experiments by other workers on graphite demonstrate that this intriguing morphology could not be the result of deformation, because graphite returns to its original shape and size on stress release. Existing experiments on diamond graphitization do not adequately replicate the conditions of natural rocks being exhumed from subduction zones characterized by ultrahigh pressures, and thus cannot be applied with confidence to the Maksyutov Complex. Our spectroscopic and microscopic studies suggest that these cuboid aggregates probably are diamond pseudomorphs.